2015
DOI: 10.1111/apt.13169
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 rs738409 I748M is associated with steatohepatitis in 434 non‐obese subjects with hepatitis C

Abstract: SummaryBackgroundThe PNPLA3/Adiponutrin rs738409 C/G single nucleotide polymorphism is associated with the severity of steatosis, steatohepatitis and fibrosis in patients with non‐alcoholic fatty liver disease, as well as the severity of steatosis and fibrosis in patients with chronic hepatitis C (CHC).AimTo test in genotype 1(G1)‐CHC patients, the putative association between the PNPLA3 variant and histological features of steatohepatitis, as well as their impact on the severity of fibrosis.MethodsFour hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
5
18
0
Order By: Relevance
“…Although Signelli et al found a relation of this SNP with steatosis in a small population [10], our finding has been replicated by others [8, 9]. This was a relatively surprising result since this genetic variant has been extensively related to non-alcoholic FLD in general population [2325] and in HCV-monoinfected patients [18, 20, 26, 27]. The relation of this genetic variant to cirrhosis without a clear association with FLD in the HIV/HCV-coinfected population could be pointing out to the existence of other factors that modulate the effect of this variant on the liver [22].…”
Section: Discussionsupporting
confidence: 73%
“…Although Signelli et al found a relation of this SNP with steatosis in a small population [10], our finding has been replicated by others [8, 9]. This was a relatively surprising result since this genetic variant has been extensively related to non-alcoholic FLD in general population [2325] and in HCV-monoinfected patients [18, 20, 26, 27]. The relation of this genetic variant to cirrhosis without a clear association with FLD in the HIV/HCV-coinfected population could be pointing out to the existence of other factors that modulate the effect of this variant on the liver [22].…”
Section: Discussionsupporting
confidence: 73%
“…The data was heterogeneous ( I 2 = 65.9%, P = 0.081), with evidence of publication bias as assessed by Begg-Mazumdar test ( P = 0.036) and tendency for publication bias as assessed by Egger test ( P = 0.059). Sensitivity analysis after excluding studies with lowest[14] and highest[49] OR revealed similar effect size: 1.82 (95%CI: 1.41-2.34) with I 2 = 18.8%, P = 0.30. Additionally, when Dual and Tweedie trim and fall test was used to assess publication bias, 3 studies were trimmed with no change in effect size (OR = 1.39, 95%CI: 1.01-1.92).…”
Section: Resultsmentioning
confidence: 85%
“…The 95%CI not crossing 1 indicates a significant association. Valenti 2012 a in panel (A) refers to reference[43], and in panel (B) refers to reference[14]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations